Factors Influencing the Performance of Nepalese Stock Market - Lamichhane, Madhusudan; Kulshrestha, Shweta (Nepal Journal of Multidisciplinary Research, 2022)
This paper investigates the effect of selected macroeconomic factors viz. remittances, money supply, exchange rate, and interest rate on stock market performance based on literatures available in international and Nepalese context. The major objective of this paper is to find out the new area of research in Nepalese perspective with the help of literature review. The study demonstrates that remittance and money supply positively affect the stock market whereas interest rate and exchange rate negatively affect the stock market performance. However, there is lack of consensus on the effect of each macro-economic variable on stock market performance as it has number of literatures available which are similar as well as opposite to these findings. Thus, similar study can be extended employing different methodology with this combination of variables in Nepalese context that may better describe and analyze the performance of Nepalese stock market and helps to reduce the confusion among the literatures.